2020
DOI: 10.1088/2053-1591/ababc0
|View full text |Cite
|
Sign up to set email alerts
|

Developing printable thermoelectric materials based on graphene nanoplatelet/ethyl cellulose nanocomposites

Abstract: Thermoelectric (TE) materials have drawn a lot of attention as a promising technology to harvest waste heat and convert it into electrical energy. However, the toxicity and expense of inorganic TE materials along with high-temperature fabrication processes have limited their application. Additionally, the reduction of raw material resources, such as metals and petroleum is another limiting factor. Hence, developing low-cost, stable, and easily-created TE materials from renewable resources is attracting more an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The electrical conductivity has an increasing trend with GNPs content. This trend can be explained by the formation of a GNPs network inside the polymer 9 . Moreover, the Seebeck coefficient increases, as the filler content increases.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The electrical conductivity has an increasing trend with GNPs content. This trend can be explained by the formation of a GNPs network inside the polymer 9 . Moreover, the Seebeck coefficient increases, as the filler content increases.…”
mentioning
confidence: 87%
“…So, thick PEDOT:PSS layers are advantageous in TE applications 7,8 . Although there are some reports of thick film or bulk form of organic TE materials 9 , it is still challenging to develop a thick or bulky high-performance PEDOT:PSS material [10][11][12][13] . The challenge relies on the limited control of their morphology and structure 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on composites consisting of graphene and other conductive polymers such as polyvinyl acetate, polypyrrole, and polyvinylidene fluoride are still ongoing 122–125 . Recently, Mardi et al 120 reported GNPs/ethyl cellulose nanocomposites for TE. Ethyl cellulose is a nonconducting polymer that is a cheap, abundant, green, and biocompatible material.…”
Section: Carbon‐based Thermoelectrics (Tes)mentioning
confidence: 99%
“…Furthermore, the maximum output powers of 16.2 and 40.1 nW were generated from the pellets at temperature differences of 20.5 and 32.3 K, respectively. The authors have taken the first step of using easily processable, low‐cost, and sustainable polymers in TE materials for commercialization in the future 120 . The TE properties of carbon allotropes (CNT, graphene) that were discussed above are summarized in Figure 12.…”
Section: Carbon‐based Thermoelectrics (Tes)mentioning
confidence: 99%